Lethrus (Heteroplistodus) kucerai (Coleoptera: Geotrupidae: Lethrinae), a new species from China - Hillert, Oliver; Král, David; Bagaturov, Mikhail; Chuluunbaatar, Gantigmaa (Zootaxa, 2024)
Lethrus (Heteroplistodus) kucerai Hillert, Král & Bagaturov, new species, from Inner Mongolia and Shaanxi provinces of China is described. Relevant diagnostic characters (e.g. genae margin, surface of head, pronotum and elytra, lateral margin of pronotum and elytra, apical spur of protibia) are compared with the morphologically similar and probably closely related species L. (H.) potanini Jakovlev, 1889. Relevant diagnostic characters including the aedeagus of both species are depicted. Lectotype for Lethrus conformis Frivaldszky, 1890 is designated. Distribution of both species from China and Mongolia is summarized and mapped.